PENGATURAN DAN PENGAWASAN PERBANKAN SYARIAH OLEH OJK DALAM RANGKA MEMPERKUAT GOOD CORPORATE GOVERNANCE (GCG) - Farhan Zikry (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2022)
Asbtract Good Corporate Governance (GCG) or good governance provides a positive value to Islamic banking. With the implementation of GCG in Islamic banking and combined with sharia principles, it is hoped that there will be improvements in performance both financially and non-financially. The purpose of this study was to determine the extent to which the regulation and supervision of the OJK in supervising the implementation of GCG in Islamic banking and how the influence of GCG on Islamic banking. The application of Good Corporate Governance in Islamic banking makes Islamic banks more Islamic. This is because Good Corporate Governance legitimizes sharia bank operations to comply with sharia principles. Keywords: Good Corporate Governance, supervision, Financial Services Authority.